Aberrant behaviours in relation to the self-reported crashes of bicyclists in China: Development of the Chinese Cycling Behaviour Questionnaire. (October 2019) - Wang, Cheng; Zhang, Weihua; Feng, Zhongxiang; Sze, N.N.; Xu, Jin; Zhang, Xuxin; Wang, Kun; Huang, Wenjuan; Luo, Yi
Highlights: A Cycling Behaviour Questionnaire designed to measure the behaviour of Chinese bicyclists is explored. The questionnaire-based investigation was conducted among 547 bicyclists in Hefei, China. Factor analysis showed that the data best fitted the four-factor solution, which explained 47.28% of the total variance. The factors were named "rule and aggressive violations", "ordinary violations", "personal control errors" and "distractions". Rule and aggressive violations, ordinary violations and distractions were related to self-reported crashes. Abstract: The current study developed the Chinese Cycling Behaviour Questionnaire (CCBQ) to measure the behaviours of Chinese bicyclists, investigated the factorial structure of aberrant cycling behaviour, and assessed which types of behaviour were related to bicyclists' self-reported crashes. The questionnaire-based investigation was conducted among 547 bicyclists in Hefei, China, and 25 items were ultimately found to have good reliability and validity. Factor analysis showed that the data best fit the four-factor solution, which explained 47.28% of the total variance. The factors were named rule and aggressive violations, ordinary violations, personal control errors and distractions . On average, male bicyclists reported higher rates of rule and aggressive violations, ordinary violations and distractions than females, and young bicyclists were more prone to these aberrant behaviours than older bicyclists. The results of multiple regression analysis indicated that rule and aggressive violations, ordinary violations and distractions were related to self-reported crashes. The implications of these findings are discussed in relation to investigating which countermeasures may effectively reduce the crash involvement of bicyclists.